Evaluation of chlorhexidine sensitization amongst healthcare workers. (26th May 2022) - Anderson, J; Fulton, R B; Li, J; Cheng, I; Fernando, S L
Abstract: Background: Chlorhexidine is an antiseptic widely used in healthcare settings. There are increasing reports of significant hypersensitivity reactions associated with its use. Development of chlorhexidine allergy has been identified as an important occupational risk to healthcare workers (HCWs). Aims: To evaluate the prevalence of sensitization to chlorhexidine amongst HCWs at a large tertiary hospital to assess the potential allergic safety risks associated with chlorhexidine exposure to staff. Methods: Sensitization to chlorhexidine was evaluated by measurement of serum-specific immunoglobulin E (IgE) in samples collected from staff assessed after a sharps-injury incident and laboratory staff collected for quality assurance procedures. This test method has been shown to have high sensitivity and specificity in the diagnosis of chlorhexidine allergy. Prevalence of sensitization was additionally evaluated with reference to changes in exposure to chlorhexidine-based hand hygiene products because of infection control procedures and the coronavirus disease 2019 pandemic. Results: A total of 320 samples were examined. The prevalence of positive chlorhexidine-specific IgE was 2%. Prevalence of sensitization in samples collected before and after increased chlorhexidine exposure was 1% and 3%. This did not represent a statistically significant difference. Conclusions: The prevalence figures for chlorhexidine sensitization in this study are higher than have been estimated previously for similar HCW cohorts. Increased exposure to chlorhexidine-based hand hygiene products was not demonstrated to increase sensitization in this group. Given the risk of severe reactions in sensitized individuals, this study indicates that evaluation of chlorhexidine allergy is important when investigating occupational allergy in HCWs.